2009
DOI: 10.1007/s11244-009-9345-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mn and Fe Addition on the NO x Storage–Reduction Properties and SO2 Poisoning of a Pt/Ba/Al2O3 Model Catalyst

Abstract: This work deals with the effect of Mn or Fe addition on the NO x storage-reduction properties of a Pt/Ba/Al 2 O 3 model catalyst. NO x storage capacity, SO 2 poisoning and regeneration and NO x removal efficiency under rich/lean cycling conditions are studied. Fe addition to Pt/Ba/Al 2 O 3 leads only to a small increase of NO x storage capacity, and more interestingly, to a better sulfur removal due to the inhibition of bulk barium sulfate formation. Unfortunately, the NO x storage property cannot be fully rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…It varies between 22 and 4% for Pt/20BaCe0.25/Al and Pt/20BaCe2/Al, respectively. These results are consistent with those obtained previously with Pt/CexZr1-xO2 catalysts[30]. It was demonstrated that the ammonia selectivity obtained in similar condition test was dependant of the ceria-zirconia composition.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…It varies between 22 and 4% for Pt/20BaCe0.25/Al and Pt/20BaCe2/Al, respectively. These results are consistent with those obtained previously with Pt/CexZr1-xO2 catalysts[30]. It was demonstrated that the ammonia selectivity obtained in similar condition test was dependant of the ceria-zirconia composition.…”
supporting
confidence: 93%
“…Concerning the ammonia selectivity, cerium could lead to lower emission. Indeed, in a recent work about the NOx storage reduction (NSR) behavior of Pt/CexZr1-xO2 catalysts, it was observed that the ammonia selectivity decreases with the increase of the cerium loading [30]. Thus, the aim of the present work is to examine the influence of Ce addition on the NSR efficiency of Pt/Ba/Al model catalyst, with a special attention for the ammonia emission.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Manganese oxide was reported to produce similar promotional effects on NSC, but no significant influence on sulfur resistance was observed 8. The addition of iron oxide was reported to improve sulfur resistance in Pt/Ba/Al 2 O 3 through inhibiting the formation of bulk barium sulfates 6a. 9 However, the co‐presence of Fe and Pt usually results in a strong deactivation 8b.…”
Section: Introductionmentioning
confidence: 99%
“…1 shows the TPR-H2 profiles of the A, A200, A400, and A600 samples. It is worth mentioning that the reduction of MnO2, in general, should be proceeded through three stages 18,19,26,28 . First, MnO2 is converted to Mn2O3 (Eq.…”
mentioning
confidence: 99%